2019
DOI: 10.1080/21623945.2019.1636624
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-induced lipid body accumulation is accompanied by lipid remodelling in model mast cells

Abstract: Mast cell lipid bodies are key to initiation, maintenance and resolution of inflammatory responses in tissue. Mast cell lines, primary bone marrow-derived mast cells and peripheral blood basophils present a 'steatotic' phenotype in response to chronic insulin exposure, where cells become loaded with lipid bodies. Here we show this state is associated with reduced histamine release, but increased capacity to release bioactive lipids. We describe the overall lipid phenotype of mast cells in this insulin-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…GPR120 enhances insulin sensitivity, regulates neutrophil activation, inhibits inflammatory macrophage infiltration, promotes the development of anti-inflammatory M2 macrophages, and enhances energy expenditure (60)(61)(62)(63). Interestingly, insulin exposure is associated with reduced histamine release, enhanced LTC 4 production, and increased resolvin D1 and E1 synthesis in RBL-2H3 cells (64). However, previous to this report, it was not known whether functional GPR40 and GPR120 were expressed by human MC.…”
Section: Discussionmentioning
confidence: 72%
“…GPR120 enhances insulin sensitivity, regulates neutrophil activation, inhibits inflammatory macrophage infiltration, promotes the development of anti-inflammatory M2 macrophages, and enhances energy expenditure (60)(61)(62)(63). Interestingly, insulin exposure is associated with reduced histamine release, enhanced LTC 4 production, and increased resolvin D1 and E1 synthesis in RBL-2H3 cells (64). However, previous to this report, it was not known whether functional GPR40 and GPR120 were expressed by human MC.…”
Section: Discussionmentioning
confidence: 72%
“…The effect of hyperglycaemia on human mast cells has been illustrated in an in vitro study, which indicated that high glucose levels promoted the phosphorylation of extracellular signal-regulated kinase, JNK, and p38 mitogenactivated protein kinases to increase the intracellular production of inflammatory cytokines such as TNFα, IL1β, and IL6 (Nagai et al 2012). The accumulation of mast cells and dendritic cells within adipose-associated connective tissue furthermore affects the healthy expansion of adipose tissue (preadipocyte differentiation), alters the release of key lipid mediators, enhances extracellular matrix protein expression/fibrosis, and contributes to the overall dysfunction of adipose tissue and subsequent insulin resistance (Żelechowska et al 2018, Aldan et al 2019, Zatterale et al 2019. This has been confirmed in animal models showing that knockout of either dendritic cells or mast cells reduces the infiltration of macrophages into adipose tissue and alleviates insulin resistance under obesogenic conditions (Liu et al 2009, Cho et al 2016.…”
Section: Dendritic Cells Mast Cells Basophils Invariant Natural Kille...mentioning
confidence: 99%
“…They are ubiquitously present across tissues, especially near surface areas like skin and close to blood and lymph vessels 1,2 . Furthermore, their ability to express a vast array of receptors enables them to respond to a wide range of stimuli, including signals from pathogens and cellular damage 3 , environmental toxins and contaminants 4,5 , immune cells 6,7 and signaling molecules [8][9][10] , neurotransmitters and neuropeptides 11,12 , as well as various hormones associated with stress responses 13,14 , metabolism 15,16 , sexual development 17,18 , and circadian rhythms 19 .…”
Section: Introductionmentioning
confidence: 99%
“…They are ubiquitously present across tissues, especially near surface areas like skin and close to blood and lymph vessels 1,2 . Furthermore, their ability to express a vast array of receptors enables them to respond to a wide range of stimuli, including signals from pathogens and cellular damage 3 , environmental toxins and contaminants 4,5 , immune cells 6,7 and signaling molecules 810 , neurotransmitters and neuropeptides 11,12 , as well as various hormones associated with stress responses 13,14 , metabolism 15,16 , sexual development 17,18 , and circadian rhythms 19 . Critically, upon activation, mast cells can release a variety of both preformed and newly synthesized mediators ranging from immune signaling molecules such as chemokines and cytokines 20 , to lipid mediators like prostaglandins and leukotrienes 21 , and neurotransmitters such as serotonin 22 , histamine 23 , and dopamine 24 , along with ATP 25 and growth factors such as VEGF 26 and NGF 27 .…”
Section: Introductionmentioning
confidence: 99%